Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Doppler Frequency Equation Question

  1. Apr 2, 2012 #1
    In my physics books it gives an equation of frequency for a moving observer as

    f'= v'/λ =v+u/λ. Since λ=v/f it was converted to f'=v+u/(v/f) = (v+u/v)f

    I understand this much of the equation, but the final Algebraic factoring that I don't get is they said this equation is f'= (1+u/v)f

    I just don't get how v+u/v was changed to 1+u/v.

    Any explanation here would be helpful.

  2. jcsd
  3. Apr 2, 2012 #2


    User Avatar
    Science Advisor
    Homework Helper

    Hi Nathan777! :smile:

    You've left out the brackets! :rolleyes:

    (Also, your dimensions obviously don't match: you can't add things of different dimensions, ie different units, eg you can't add a v to a u/λ. :wink:)

    It should be written …

    f'= v'/λ =(v+u)/λ. Since λ=v/f it was converted to f'=(v+u)/(v/f) = ((v+u)/v)f = (1 + u/v)f​
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook